Asymmetric Mannich reactions of (S)-N-tert-butylsulfinyl-3,3,3-trifluoroacetaldimines with yne nucleophiles - Li, Ziyi; Wang, Li; Huang, Yunqi; Mei, Haibo; Konno, Hiroyuki; Moriwaki, Hiroki; Soloshonok, Vadim A.; Han, Jianlin (Beilstein Journal of Organic Chemistry, 2020)
In the present work, arylethynes were studied as new C-nucleophiles in the asymmetric Mannich addition reactions with (S)-N-tert-butylsulfinyl-3,3,3-trifluoroacetaldimine. The reactions were conducted under operationally convenient conditions affording the corresponding Mannich adducts with up to 87% yield and 70:30 diastereoselectivity. The isomeric products can be separated using regular column chromatography to afford diastereomerically pure compounds. The purified Mannich addition products were deprotected to give the target enantiomerically pure trifluoromethylpropargylamines. A mechanistic rationale for the observed stereochemical outcome is discussed.
Keywords: arylethynes; asymmetric Mannich reaction; C-nucleophile; CF3-aldimine; fluorinated propargylamine